2018
DOI: 10.1136/bmjqs-2018-008661
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the Hospital Frailty Risk Score and comparison with the Hospital-patient One-year Mortality Risk Score to predict outcomes in elderly hospitalised patients: a retrospective cohort study

Abstract: ObjectiveFrailty is an important prognostic factor in hospitalised patients but typically requires face-to-face assessment by trained observers to detect. Thus, frail patients are not readily apparent from a systems perspective for those interested in implementing quality improvement measures to optimise their outcomes. This study was designed to externally validate and compare two recently described tools using administrative data as potential markers for frailty: the Hospital Frailty Risk Score (HFRS) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
100
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 18 publications
8
100
2
Order By: Relevance
“…Secondly, the addition of the HFRS to standard risk prediction equations [2,3] for postdischarge outcomes provided little additional information in our cohort. This echoes an earlier report [6] that the HFRS only poorly predicted outcomes in the first 30 days after discharge in 452 785 hospitalized elderly patients in another Canadian province. Like that earlier study, we also found that the HFRS was a better predictor of prolonged hospital stay in this cohort than postdischarge outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Secondly, the addition of the HFRS to standard risk prediction equations [2,3] for postdischarge outcomes provided little additional information in our cohort. This echoes an earlier report [6] that the HFRS only poorly predicted outcomes in the first 30 days after discharge in 452 785 hospitalized elderly patients in another Canadian province. Like that earlier study, we also found that the HFRS was a better predictor of prolonged hospital stay in this cohort than postdischarge outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…The hospital frailty risk score (range 0-50) is a comprehensive and validated measure of a patient’s function and comorbidity that reflects global illness severity and identifies a group of patients who are at greater risk of adverse outcomes, including hospital admission and 30 day mortality 42. We categorised hospital frailty scores into four groups based on the distribution of scores within our cohort: 0, 0.1-8.9, at least 9, and not admitted to hospital 4246. We did not account for clustering by physician or facility because most people receive end-of-life care from several physicians in multiple care settings.…”
Section: Methodsmentioning
confidence: 99%
“…(ICD-10) coding system [13], was developed for frailty risk stratification among older hospitalized patients and has been validated for its ability to predict adverse outcomes in various settings [14,15].…”
Section: International Statistical Classification Of Diseases and Relmentioning
confidence: 99%